Ownership and use of wireless telephones: a population-based study of Swedish children aged 7-14 years - Carlberg Michael; Hardell Lennart; Söderqvist Fredrik; Hansson Mild Kjell (BMC, 2007)
Abstract Background Recent years have seen a rapid increase in the use of mobile phones and other sources of microwave radiation, raising concerns about possible adverse health effects. As children have longer expected lifetime exposures to microwaves from these devices than adults, who started to use them later in life, they are a group of special interest. Methods We performed a population-based study to assess ownership and use of mobile phones and cordless phones among children aged 7-14 years. A questionnaire comprising 24 questions was sent to 2000 persons selected from the Swedish population registry using a stratified sampling scheme. Results The response rate was 71.2%. Overall, 79.1% of the respondents reported mobile phone access, and 26.7% of them talked for 2 minutes or more per day. Of those who reported mobile phone access, only 5.9% reported use of hands-free equipment. Use of cordless phones was reported by 83.8% of the respondents and 38.5% of them talked for 5 minutes or more per day. Girls generally reported more frequent use than boys. Conclusion This study showed that most children had access to and used mobile and cordless phones early in life and that there was a rapid increase in use with age. It also showed very low use of hands-free equipment among children with mobile phone access, and finally that girls talked significantly more minutes per day using mobile and cordless phones than boys did.